2019
DOI: 10.1002/jcsm.12450
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages protect against loss of adipose tissue during cancer cachexia

Abstract: BackgroundCancer cachexia represents a central obstacle in medical oncology as it is associated with poor therapy response and reduced overall survival. Systemic inflammation is considered to be a key driver of cancer cachexia; however, clinical studies with anti‐inflammatory drugs failed to show distinct cachexia‐inhibiting effects. To address this contradiction, we investigated the functional importance of innate immune cells for hepatocellular carcinoma (HCC)‐associated cachexia.MethodsA transgenic HCC mous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 64 publications
(126 reference statements)
1
22
1
Order By: Relevance
“…Functional studies in cancer patients have found a positive relationship between immune cell infiltration (granulocyte/phagocytes, and CD3−CD4+ cells) and muscle mass status, whereas a negative correlation has been established between CD8 T cells and muscle catabolic pathways [40]. In a murine HCC (Hepatocellular Carcinoma) model, a decreased macrophage infiltration in visceral tissue has been associated with the loss of adipose tissue [39,41], whereas in clinical studies, activated macrophages have been found to be infiltrated in fat. To date, the mechanisms by which macrophages modulate adipocyte function are still unclear [42][43][44][45].…”
Section: Immune Systemmentioning
confidence: 99%
“…Functional studies in cancer patients have found a positive relationship between immune cell infiltration (granulocyte/phagocytes, and CD3−CD4+ cells) and muscle mass status, whereas a negative correlation has been established between CD8 T cells and muscle catabolic pathways [40]. In a murine HCC (Hepatocellular Carcinoma) model, a decreased macrophage infiltration in visceral tissue has been associated with the loss of adipose tissue [39,41], whereas in clinical studies, activated macrophages have been found to be infiltrated in fat. To date, the mechanisms by which macrophages modulate adipocyte function are still unclear [42][43][44][45].…”
Section: Immune Systemmentioning
confidence: 99%
“…The pro-cachectic acute phase response is not seen, however, in 66C4 subclone of 4TI mice in which MDSC expansion does not occur [53] . Defects in myeloid cell-mediated inflammation has also been shown to result in reduced expression of pro-inflammatory cytokines in the serum of mice with hepatocellular carcinoma [54] . Interestingly, this led to enhanced loss of adipose tissue and decreased macrophage number in visceral adipose tissue, suggesting a possible local role for macrophages in the regulation of cancer-induced fat loss [54] .…”
Section: Myeloid Derived Suppressor Cellsmentioning
confidence: 99%
“…Defects in myeloid cell-mediated inflammation has also been shown to result in reduced expression of pro-inflammatory cytokines in the serum of mice with hepatocellular carcinoma [54] . Interestingly, this led to enhanced loss of adipose tissue and decreased macrophage number in visceral adipose tissue, suggesting a possible local role for macrophages in the regulation of cancer-induced fat loss [54] . These findings imply that myeloid cell-mediated inflammation confers a beneficial function in these rodents, and may provide a potential explanation for the failure of several antiinflammatory drugs in treating cachexia.…”
Section: Myeloid Derived Suppressor Cellsmentioning
confidence: 99%
“…Potential biomarker should not only be predictive but should also allow to monitor the progression of cachexia and the effects of putative therapies. However, while there are a number of biomarker candidates (for comprehensive overview, see Loumaye and Thissen 2 ) such as TGF‐β, 3 activin A, 4 myostatin, 5,6 systemic inflammation, 7 pro‐inflammatory cytokines and chemokines, 8–10 micro RNAs, 11–18 and protein degradation products, 19–21 none have been clinically established, except for the hallmark symptom weight loss in combination with additional factors such as muscle mass and strength 22 . In addition, markers of fat loss such as leptin, 23,24 free fatty acids, 25,26 glycerol, 27 and zinc‐α2‐glycoprotein 28 may be of clinical interest.…”
mentioning
confidence: 99%